CUSTEIO BASEADO EM ATIVIDADES - ABC - FRANCISCONI, TÁLISSON RENATO DIDONÉ; GONÇALVES, JEAN LUCAS DE OLIVEIRA; COSTA, GABRIEL DORNELLES; SCHUH, PATRICIA LUIZA (Salão do Conhecimento, 2025)
CUSTEIO BASEADO EM ATIVIDADES - ABC